2019
DOI: 10.1177/0886260519847776
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Severe Violence in Intimate Partner Stalking Situations: An Analysis of Police Records

Abstract: Stalkers can be violent, and empirical studies have sought to identify factors associated with violence perpetrated by the stalker. Most of these works view physical violence as a homogenous construct, and do not differentiate between moderate and severe violence. The present study aims to identify correlates of non-violent, moderate, and severe physical violence within an archival sample of 369 domestically violent police incident reports, where stalking behavior was indicated. The incident reports utilized i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 46 publications
1
20
0
Order By: Relevance
“…In the sample of the present study, many women (six out of 10) had decided to end the relationship, and some had filed a complaint against the abuser (three out of 10). Nevertheless, as the findings of this study reveal, S-IPV from antisocial aggressors hardly ever ends after the breakup; on the contrary, the antisocial aggressor usually increases his controlling behavior and stalking of the victim (Bendlin & Sheridan, 2019). In addition to the reasons cited above that contribute to a victim’s decision not to file a complaint against her aggressor (minimizing, guilt, and legal issues), the present study highlights the influence of the aggressor’s threats and coercive behaviors in making the victim withdraw the complaint, as Echeburúa et al (2008) pointed out in a prior study.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…In the sample of the present study, many women (six out of 10) had decided to end the relationship, and some had filed a complaint against the abuser (three out of 10). Nevertheless, as the findings of this study reveal, S-IPV from antisocial aggressors hardly ever ends after the breakup; on the contrary, the antisocial aggressor usually increases his controlling behavior and stalking of the victim (Bendlin & Sheridan, 2019). In addition to the reasons cited above that contribute to a victim’s decision not to file a complaint against her aggressor (minimizing, guilt, and legal issues), the present study highlights the influence of the aggressor’s threats and coercive behaviors in making the victim withdraw the complaint, as Echeburúa et al (2008) pointed out in a prior study.…”
Section: Discussionmentioning
confidence: 58%
“…P. Johnson, 2008; Monckton-Smith, 2019). This may explain why some meta-analytic studies have found that controlling behaviors, jealousy, stalking, power display, and patriarchal beliefs are strong risk markers for S-IPV (Bendlin & Sheridan, 2019; Love et al, 2018; Spencer & Stith, 2018). Recent research has also identified other aggressor-related risk factors for S-IPV, such as an increase in the severity of the abuse, severe physical abuse, suicide threats or attempts (Campbell et al, 2009), degrading treatment, a breakdown of victim protection measures, aggressions against other relatives (Echeburúa et al, 2009), sexual assault or abuse, death threats, substance abuse, and mental disorders (Spencer & Stith, 2018).…”
Section: Risk Factors For Perpetrating S-ipvmentioning
confidence: 99%
See 1 more Smart Citation
“…Among stalkers, acts of aggression and violence are estimated to occur in 25–50% of offences, although this rate is said to increase if the victim and offender had a prior intimate relationship (Bendlin & Sheridan, 2019; Farnham et al, 2000; Logan, 2020a; McEwan et al, 2017; Meloy, 1996; Meloy & Boyd, 2003; Meloy et al, 2011; Meloy & Gothard, 1995; Mullen et al, 2000; Purcell et al, 2001, 2010; Rosenfeld & Lewis, 2005; Strand & McEwan, 2012; Thompson et al, 2020). Studies have noted similar rates of violence across male- and female-adult stalkers (Purcell et al, 2001; Scott et al, 2015; Strand & McEwan, 2012) as well as among juvenile stalkers (Purcell et al, 2010).…”
Section: Behavior and Motivationmentioning
confidence: 99%
“…Indeed, Strand and McEwan (2012) found that the combination of a prior intimate relationship, approach behaviors, and threats best predicted violence for both male and female stalkers. Other general risk factors for violence which hold true for female stalkers include an opposite-gender victim, explicit threats, previous criminal history or violent history, and dynamic factors such as substance abuse, triggering events, intentions, and opportunities (Bendlin & Sheridan, 2019; Farnham et al, 2000; Meloy, 2002; Meloy & Boyd, 2003; Meloy et al, 2011; Strand & McEwan, 2012; Thompson et al, 2020).…”
Section: Behavior and Motivationmentioning
confidence: 99%